Nanomaterials in the Context of Type 2 Immune Responses—Fears and Potentials - Himly, Martin; Mills-Goodlet, Robert; Geppert, Mark; Duschl, Albert (Frontiers in Immunology, 2017)
Preface The type 2 immune response is an adaptive immune program involved in defense against parasites, detoxification and wound healing, but is predominantly known for its pathophysiological effects, manifesting as allergic disease. Engineered nanoparticles are non-self entities that, to our knowledge, do not stimulate detrimental type 2 responses directly, but have the potential to modulate ongoing reactions in various ways, including the delivery of substances aiming at providing a therapeutic benefit. We review here the state of knowledge concerning the interaction of nanoparticles with type 2 immune responses and highlight their potential as a multifunctional platform for therapeutic intervention.